A correlation for heat transfer during boiling on bundles of horizontal plain and enhanced tubes. (June 2017) - Shah, Mirza M.
Highlights: Correlation for saturated boiling on bundles of plain and enhanced tubes is presented. Mean deviation 15.2% for 2173 data points from 51 data sets from 28 sources is predicted. Data include 12 fluids, staggered and inline bundles, and pitch/diameter 1.17 to 2. This is the only correlation applicable to both plain and enhanced tubes. Abstract: A dimensionless correlation is presented for calculation of local heat transfer coefficients during saturated boiling in bundles of plain and enhanced tubes. It has been verified with a wide range of data that include 12 fluids (water, ammonia, halocarbon refrigerants, and hydrocarbons), plain and a variety of enhanced tubes of many materials, inline and staggered arrangements, pitch to diameter ratios 1.17 to 2.0, reduced pressures from 0.005 to 0.2866, mass flux from 0.17 to 1391 kgm −2 s −1, heat flux from 1 to 1000 kWm −2, and vapor quality from 0 to 0.98. A total of 2173 data points from 51 data sets from 28 sources are predicted with mean absolute deviation of 15.2%.